Aloe vera extract wound healing sheet and free-range chicken egg albumin (gallus domesticus) accelerate angiogenesis on gingival incision wound in rats - Putri, Myrna Evana Amanda; Prihastuti, Christiana Cahyani; Rochmawati, Mutia; Rosyada, Alya Ghina; A'ziza, Wizni A'dila (Padjadjaran Journal of Dentistry, 2023)
ABSTRACTIntroduction: Incision wounds are injuries caused by dental surgery procedures. Suturing is the gold standard for post-incision management, but it can cause patient discomfort. Tissue glue can be used for wound healing, but its carcinogenicity still needs to be investigated. A Wound Healing Sheet (WHS) made of Aloe vera extract and free-range chicken egg albumin is expected to be an alternative material. Angiogenesis is a highly observable part of wound healing, as newly formed blood vessels support nutrition, act as a scaffold for cells to migrate to the wound area, and play an essential role in wound healing. This study aimed to analyze the effect of WHS made from Aloe vera extract and free-range chicken egg albumin (Gallus domesticus) on the number of vascular that show the acceleration of healing in gingival incision wounds. Methods: Quasi experimental study with a total sample of 24 male rats (Rattus norvegicus Wistar strain) with gingival incision were divided into four groups, namely T1 (50% WHS treated group), T2 (100% WHS treated group, S (suturing treated group as positive control), and NC (negative control, without treatment). The treatment was performed throughout seven days. The data obtained were analyzed statistically using One-way ANOVA and Post Hoc LSD. Results: The highest vascular count was in the T2 Group (8+1.63); followed by T1 (7+1.60); S (7+ 1.49); and NC (4+1.41). Statistical analysis showed that there was a significant difference between groups S, T1, T2 with NC (p-value < 0.05); interestingly, there was no significant difference between S, T1, T2 (p-value > 0.05). Conclusion: Wound Healing Sheet made of Aloe vera extract and free-range chicken egg albumin (Gallus domesticus) can accelerate the angiogenesis process on gingival incision wound in rats.Keywords: wound healing, aloe vera, gallus domesticus, egg white, angiogenesis